2018
DOI: 10.1590/1806-9126-rbef-2018-0206
|View full text |Cite
|
Sign up to set email alerts
|

A study of strain and deformation measurement using the Arduino microcontroller and strain gauges devices

Abstract: This paper presents a methodology for the measurement of strain by means of strain-gauges, where the data acquisition is done by using an Arduino Uno board, due to the low-cost and the easy manipulation of this microcontrollers. The measured signal conditioning is performed by means of a Wheatstone Bridge and then discretized by an Analog-Digital Converter (ADC) external to the Arduino. For the validation of the proposed measurement system, experiments are performed on a cantilever beam and on a cantilever-sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
0
7
0
3
Order By: Relevance
“…Dessa forma, deformações em várias partes de uma estrutura real sob condições de serviço podem ser medidas com boa precisão sem que a estrutura seja destruída. Assim, pode-se realizar uma análise quantitativa da distribuição da deformação sob condições reais de operação (Andolfato, 2004;Silva, 2019).…”
Section: Extensometriaunclassified
“…Dessa forma, deformações em várias partes de uma estrutura real sob condições de serviço podem ser medidas com boa precisão sem que a estrutura seja destruída. Assim, pode-se realizar uma análise quantitativa da distribuição da deformação sob condições reais de operação (Andolfato, 2004;Silva, 2019).…”
Section: Extensometriaunclassified
“…This process involves three phases, namely signal collection, signal processing and result analysis. Regrettably, a fatigue signal is not easy to be obtained directly, and the acquisitions bear a high cost and consume a lot of time [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…the metal platens) plus the rock specimen. Therefore, the strain of the metal platens should always be subtracted in the first instance using preliminary calibration charts to avoid an overestimation of the sample's true deformation (Silva et al 2019). Alternatively, direct measurement methods through strain gauging technique can be adopted.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, direct measurement methods through strain gauging technique can be adopted. However, given that strain gauges are relatively expensive and non-reusable, it could make the overall cost of the experimentation more expensive (Silva et al 2019). Further, it has been shown that the direct measurement of sample deformation under three-dimensional stress conditions is extremely difficult in practice.…”
Section: Introductionmentioning
confidence: 99%